2013
DOI: 10.5001/omj.2013.38
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Standard Precautions and Awareness Regarding Post-Exposure Prophylaxis for HIV among Interns of a Medical College in West Bengal, India

Abstract: The considerable gap between knowledge and practice of standard precautions and inadequate knowledge of post-exposure prophylaxis emphasizes the need for continuous onsite training of interns with supportive supervision and monitoring of their activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
33
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 10 publications
4
33
3
Order By: Relevance
“…15 Further research showed that nurses working in BPKMCH were less aware of the first aid management in comparison to the previous study. 16 Most of the respondents have knowledge on body fluids, which are considered as high risk for HIV transmission. A similar finding was reported in Medical College in West Bengal of India, which showed that pleural fluid was considered infectious by 53%, cerebrospinal fluid by 55% and synovial fluid by 37%, whereas 53% considered peritoneal fluid, 79% breast milk, 14% saliva, 27% urine, 27% feces, and 21% vomits to be infectious.…”
mentioning
confidence: 99%
“…15 Further research showed that nurses working in BPKMCH were less aware of the first aid management in comparison to the previous study. 16 Most of the respondents have knowledge on body fluids, which are considered as high risk for HIV transmission. A similar finding was reported in Medical College in West Bengal of India, which showed that pleural fluid was considered infectious by 53%, cerebrospinal fluid by 55% and synovial fluid by 37%, whereas 53% considered peritoneal fluid, 79% breast milk, 14% saliva, 27% urine, 27% feces, and 21% vomits to be infectious.…”
mentioning
confidence: 99%
“…Whereas in a study by Mukherjee S et al showed that 89.2% of study participants knew appropriate sharp disposal and 83.1% knew that recapping of used needles should not be done which were very high compared to our study. 9 In the same study by Mukherjee S et al it was shown that 68.5% of study participants correctly knew the time of initiation of PEP for HIV, 69.2% knew PEP regimen correctly which were very high. 9 Whereas in our study 44% answered correctly the time of initiation and 23% knew correct recent NACO regimen.…”
Section: Discussionmentioning
confidence: 86%
“…9 In the same study by Mukherjee S et al it was shown that 68.5% of study participants correctly knew the time of initiation of PEP for HIV, 69.2% knew PEP regimen correctly which were very high. 9 Whereas in our study 44% answered correctly the time of initiation and 23% knew correct recent NACO regimen.…”
Section: Discussionmentioning
confidence: 86%
“…There were no studies to compare the fi ndings of the present study regarding awareness about and personal protection from EVD in health care providers, though Nkoghe et al in his study in Africa did show that increased awareness helped in early interruption of spread of EVD. [7] The knowledge among health care providers about the importance of personal protection from Ebola virus in the present study is comparable to that seen in other infectious diseases such as HIV [11] and swine fl u. [12] The study had some limitations.…”
Section: Discussionmentioning
confidence: 89%